Design and construction of a one-axis sun-tracking system - Kalogirou, Soteris A. (My University, 1996)
This paper describes a tracking system which can be used with single-axis solar concentrating systems. The position and “status” of the Sun are detected by three light-dependent resistors (LDRs), one of which detects whether the collector is focused, whilst a second resistor determines if there is cloud cover, and the third senses whether it is day or night. The resultant signals are fed to an electronic control system which operates a low-speed 12-V d.c. motor which rotates the collector via a speed-reduction gearbox. The tracking system accuracy depends on the magnitude of the solar irradiance. The deviation from zero is 0.2 and 0.05° with solar radiation of 100 and 600 W m−2, respectively. Both values suggest that the mechanism can be used satisfactorily for parabolic trough collectors of medium to high concentration ratios.
Keywords: Tracking system